D-lactate is a promising biomarker for the diagnosis of periprosthetic joint infection - Fuchs, M.; Faschingbauer, M.; Riklin-Dold, M.; Morovic, P.; Reichel, H.; Trampuz, A.; Karbysheva, S. (Frontiers in Surgery, 2022)
Introduction: Reliable biomarkers for the diagnosis of periprosthetic joint infection (PJI) are of paramount clinical value. To date, synovial fluid leukocyte count is the standard surrogate parameter indicating PJI. As D-lactate is almost solely produced by bacteria, it represents a promising molecule in the diagnostic workflow of PJI evaluation. Therefore, the purpose of this study was to assess the performance of synovial fluid D-lactate for diagnosing PJI of the hip and knee. Materials and Methods: These are preliminary results of a prospective multicenter study from one academic center. Seventy-two consecutive patients after total hip arthroplasty (THA) or total knee arthroplasty (TKA) were prospectively included. All patients received a joint aspiration in order to rule out or confirm PJI, which was diagnosed according to previously published institutional criteria. Synovial fluid D-lactate was determined spectrophotometrically at 450 nm. Receiver operating characteristic (ROC) analysis was performed to assess the diagnostic performance. Results: Eighteen patients (25%) were diagnosed with PJI and 54 patients (75%) were classified as aseptic. Synovial fluid D-lactate showed a sensitivity of 90.7% (95% CI: 79.7% - 96.9%) and specificity of 83.3% (95% CI: 58.6% - 96.4%) at a cut-off of 0.04 mmol/l. The median concentration of D-lactate was significantly higher in patients with PJI than in those with aseptic conditions (0.048 mmol/l, range, 0.026 - 0.076 mmol/l vs. 0.024 mmol/l, range, 0.003 - 0.058 mmol/l, p <0.0001). The predominat microogranisms were staphylococci, followed by streptococci and gram-negative bacteria. Conclusion: D-lactate bears a strong potential to act as a valuable biomarker for diagnosing PJI of the hip and knee. In our study, a cutoff of 0.04 mmol/l showed a comparable sensitivity to synovial fluid leukocyte count. However, its specificity was higher compared to conventional diagnostic tools. The additional advantages of D-lactate testing are requirement of low synovial fluid volume, short turnaround time and low cost.